PENERAPAN METODE APPLIED BEHAVIOUR ANALYSIS (ABA) UNTUK ANAK AUTISME PADA PEMBELAJARAN AL-QUR'AN DI SEKOLAH DASAR ISLAM TERPADU PERMATA KOTA PROBOLINGGO - Yunusiyah, Rahmah El; Muhammad, Devy Habibi (IMTIYAZ: Jurnal Ilmu Keislaman, 2024)
The Applied Behavior Analysis (ABA) method is employed to modify children's behavior, particularly those with autism, emphasizing positive reinforcement and firmness without resorting to violence. At SDIT Permata, the ABA method is applied in the Al-Qur'an learning process with the aim of assisting autistic children in understanding the Arabic alphabet and memorizing the Quran. This approach involves direct learning, creating specific situations, and conducting instructional activities. The Amanah Foundation, founded by Mr. Ir. Agung Sasongko, supports inclusive education as an expression of compassion for children with special needs. This research aims to explore the implementation of the ABA method in Quranic learning for autistic children at SDIT Permata and identify supporting and inhibiting factors. The research methodology employed in this study is descriptive qualitative field research. The results indicate that the implementation of the ABA method involves direct approaches, specifically designed situations, and instructional activities. Teachers provide consistent instructions, utilize positive reinforcement, and offer guidance based on individual needs. Supporting factors include teacher involvement, praise, and learning through planned situations, while inhibiting factors involve tantrums, difficulties in interaction, and unstable emotional conditions in children. This research is expected to contribute positively to the development of inclusive education in Indonesia. Keywords:  ABA Method; Quranic Learning; Autistic Children.